The challenges and issues of e-government in Indonesia from citizen's perspective - Endang, A (Institut Teknologi Sepuluh Nopember, 2018)
Each ministry and local government in Indonesia has a separate service to serve the citizens. But with the e-government ministries and local government should be able to further improve public services for citizens and centralized. In this research will be analyzed on the challenges and issues that occurred in Indonesia from the perspective of service for citizen in order to avoid unnecessary inconvenience and red tape in regard to moving, living, studying, working, shopping or simply travelling abroad. Analyze in this research using qualitative method to describe the current condition of each element especially in challenges and issues that occurs. The groups of services for citizens that analyzed in this research are Travel, Work and Retirement, Vehicles, Residence formalities, Education and Youth, Health, Family consumers which results from this research could leads government to focus on improvements to enhance public services for citizens.